Peningkatan Hasil Belajar Pengukuran Panjang dan Berat Menggunakan Model Realistic Mathematic Education di Kelas IV SDN 05 Air Tawar Barat Kota Padang: Indonesia - Amanda, Fuji; Zainil, Melva (Indo-MathEdu Intellectuals Journal, 2025)
This research is motivated by the planning and implementation of learning on measuring length and weight carried out by teachers that are not optimal, resulting in low learning outcomes for students in grade IV of SDN 05 Air Tawar Barat, Padang City. This study aims to describe the improvement in learning outcomes on measuring length and weight using the Realistic Mathematics Education model in grade IV of SDN 05 Air Tawar Barat, Padang City. This research is a classroom action research  using two types of approaches, namely a qualitative approach and a quantitative approach. The research was conducted in two cycles, cycle I with II meetings and cycle II with I meeting. The results of the study showed an increase in a) the cycle I teaching module obtained an average percentage of 87.5% increasing in cycle II to 95.83%, b) teacher activity in cycle I obtained an average percentage of 83.33% increasing in cycle II to 95.83%, c) student activity obtained an average percentage of 79.16% then increased in cycle II to 91.66%, d) student learning outcomes in cycle I obtained an average learning outcome of 76.48 with a predicate (C). Then increased in cycle II to 85.64 with a predicate (B). Based on these results, it can be concluded that Realistic Mathematics Education can improve student learning outcomes in the material on Length and Weight Measurement.